Classical and Approximate Theorems of Weighted Space Sampling - et. al., Ban Mohammad Hassan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We show the same findings in this article, for the authors introduced in 2005 and 2004 that proved the classical sampling theorems, in the space ,and Bulzer show that three variants of the indicative analysis sampling theorem are similar in the significance that one can be shown as a corollary of one of the others. in 2014 [1] and [2], but in this work for any function in the space the space of all functions which are integral by weight function. Consequently, the two sampling theorems in the universal standard are fully identical. The outcome seems to be that our work is successful